Islam in human resources management and organizational behavior discourses - Linando, Jaya Addin (Asian Management and Business Review, 2022)
The importance of religion in management studies is rising and is better appreciated nowadays. As one of the major acknowledged and one of the most misunderstood religions globally, Islam and all things related to Muslims in the workplace should also gain more attention from the management scholars to promote better understanding and mutual respect. This paper tries to answer the broad question of ‘what are the main themes of Islam in Human Resources Management (HRM) and Organizational Behavior (OB) discourses?’. The paper identifies three focal themes within the topic: current workplace circumstances for Muslims; Islamic religiosity from HRM and OB perspectives; and Islamic viewpoint of work. Through the narrative review approach, this paper establishes three contributions. The first contribution is to discuss the essential issues of Islam and Muslims in HRM and OB discourses. Second, this paper bridges the contemporary HRM-OB discourses and Islamic teachings. Third, this paper suggests possible discussion points for further advancement of Muslims in the workplace topic.